Mathematical Spatial Ability Reviewed from Students’ Self-Confidence in the PBL Model with Teacher and Peer feedbacks Assisted by Geogebra (Unnes Journal of Mathematics Education Research, 2021)
This research aims to describe mathematics spatial skill reviewed from the self-confidence of students in high, moderate, and low categories. This research was conducted in the eighth grade JHS Hasannudin 6 Semarang, in the academic year 2018/2019. This mixed-method research used a sequential explanatory strategy. It is a procedure to collect quantitative and qualitative data orderly. The technique of collecting quantitative data was done by mathematics-spatial skill test. Meanwhile, the qualitative data was done by documentation, questionnaire, and interview. The findings showed mathematics-spatial skill of each-category student’s self-confidence had various mastery indicators. The students with high-self-confidence tended to be more consistent in mastering spatial visualization, spatial relation, and mental rotation. The spatial-orientation and spatial-perception aspects of high self-confidence students were sometimes successful and sometimes not successful. The moderate-self-confidence students tended to master spatial visualization, spatial relation, and spatial orientation aspects. However, there were several subjects with moderate-self confidence in the five aspects. Subjects with low-self-confidence tended to be more consistent in mastering spatial visualization and spatial perception. There were subjects with low-self-confidence who only mastered four aspects of mathematics-spatial skills.